The Influence of Omni-Directional Guide Vane on the Cross - Flow Wind Turbine Performance - Yahya, Yahya; Fahrudin, Fahrudin; Martana, Budhi (International Journal of Marine Engineering Innovation and Research, 2024)
As cities grow, the demand for energy increases, necessitating a corresponding increase in energy supply. Since urban areas consume the majority of the world’s energy, switching to renewable energy sources is essential. Wind energy is one of the most popular renewable energy sources for generating electricity. Vertical-axis wind turbines (VAWTs) are used in urban areas due to their advantages, with cross-flow wind turbines (CFWTs) being one type. However, the efficiency of CFWTs is relatively low, necessitating the application of augmentation devices. This study aims to find the optimal configuration between CFWTs and Omni-Directional Guide Vanes (ODGV), using 6DOF dynamic mesh methods in ANSYS Fluent with varying the turbine blade counts and the addition of ODGV. The results showed that the 18-blade configuration exhibits the highest improvement with ODGV, demonstrating a remarkable 71 percent increase in the power coefficient. In general, the highest performance is achieved by the 20-blade turbine with a 6-blade ODGV configuration, with a power coefficient of 0.2455, which is 30 percent higher than the baseline 20-blade turbine. These findings indicate that the addition of ODGV significantly improves the performance of cross-flow wind turbines.